Effect of platelet lysate on the functional and molecular characteristics of mesenchymal stem cells isolated from adipose tissue - Castegnaro, Silvia; Chieregato, Katia; Maddalena, Marta; Albiero, Elena; Visco, Carlo; Madeo, Domenico; Pegoraro, Maurizio; Rodeghiero, Francesco (Current stem cell research & therapy, 2011)
Mesenchymal stem cells (MSCs) are non-hematopoietic, adult, fibroblast-like, multipotent cells that are plastic adherent in standard culture conditions. They can be isolated from several tissues, but it is always necessary to expand them for clinical practice. We investigated the effect of human platelet lysate (hPL) on the expansion of human MSCs isolated from adipose tissue (AT), comparing it with fetal bovine serum (FBS) and human platelet-poor plasma (hPPP). Human AT-MSCs, hPL and hPPP were obtained from 7 healthy subjects. AT-MSCs were seeded at 1500 cells/cm(2) and cultured in Dulbecco's modified Eagle's medium supplemented with 10% FBS, 10% hPPP or 10% hPL. Cells were harvested, counted and analyzed by flow cytometry every 7 days for 5 passages (P). The differentiation assays, RNA isolation and co-culture with allogeneic lymphocytes were performed at the end of P2. AT-MSCs achieved a better proliferation rate when cultured with hPL than with hPPP or FBS (20 ±2 versus 8 ±3 and 6 ±3, respectively, at the end of P5 [p<0.01]). hPL preserved the differentiation capacity and typical expression of surface antigens, avoiding the risks associated with the use of animal derivatives. AT-MSCs demonstrated a stronger inhibitory effect on lymphocyte proliferation with hPL than with other culture conditions, even at a AT-MSCs:T cells ratio of 1:10. The transcriptional level of matrix metalloproteinase 2, used to evaluate stemness, was very high in all conditions tested. hPL represents an effective and safe supplement for MSC expansion to be used in the clinical setting.